Protecting Biodiversity via Metaphysical Angels of the Future - Louisson, Amalia (Identities: Journal for Politics, Gender and Culture, 2020)
Global trends in contemporary left biodiversity protection practices are self-undermining because they are fixated on resurrecting past ecological conditions, while failing to prepare for the future. Not only will many species be unable to survive in predicted future conditions, but focusing on the past has forfeited the future to capital. Instead, this paper presented at the ISSHS School for Politics and Critique 2020 takes the recently resurrected figure of Prometheus to promote an environmentalism that casts its eyes to the future. It will be argued that preparing the future for biodiversity can sever capital’s claim over the future by prompting a traumatic instance of physicality. Author(s): Amalia Louisson Title (English): Protecting Biodiversity via Metaphysical Angels of the Future Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 2-3 (Winter 2020) Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 76-80 Page Count: 5 Citation (English): Amalia Louisson, “Protecting Biodiversity via Metaphysical Angels of the Future,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 2-3 (Winter 2020): 76-80. Author Biography Amalia Louisson, University of Melbourne Amalia Louisson is a teacher, researcher, and Political Science PhD student at the University of Melbourne. Her research focuses on the relationship between psychoanalytic fantasies and environmental degradation, and how confronting the nihilism of the real can spur the conceptual and technological innovation needed to address that degradation. She advocates reconnecting philosophy with real politics and the future.